Assessment of Resources in Baghmara Community Forest of Central Lowland Nepal - Sharma, Bhuvan Keshar; Chalise, Mukesh Kumar (Journal of Natural History Museum, 2015)
Initial assessment of cost and benefit aspect to the community managed forest for biodiversity conservation was conducted in Baghmara Community Forest at central lowland Nepal. Wildlife was being colonizing and forest was in early succession stage. The area was potential habitat for large wildlife too. Cost-benefit analysis indicated more cost than benefit during the initial stage. Eco-tourism was initiated after a few conservation management efforts in the area that resulted the numbers of tourist influx which will be on profit in near future. J. Nat. Hist. Mus. Vol. 26, 2012: 163-174